Management of Insect and Mite Resistance in Ornamental Crops - James F. Price; Elzie McCord, Jr.; Curtis Nagle (EDIS)
Resistance of arthropods to crop management chemicals has been problematic since the early era of synthetic organic pesticides. During the 1970s and early 1980s leafminer outbreaks heavily damaged herbaceous ornamental crops such as chrysanthemum, gypsophila, aster, and marigold in fields, shade houses and greenhouses. Several effective insecticides including organophosphates, carbamates, pyrethroids, and a triazine were identified for leafminer control during the outbreak; however, control was short-lived as the leafminer developed resistance to each insecticide. This 11-page fact sheet was written by James F. Price, Elzie McCord, Jr., and Curtis Nagle, and published by the UF Department of Entomology and Nematology, November 2012.